Was the Great Irish Famine a Colonial Famine? - Gray, Peter (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
This article reviews the historical debate on the colonial causation and dimensions of the Great Irish Famine of 1845-50. It does so by briefly reviewing the evolution of the colonial relationship between Great Britain and Ireland before focusing on a number of specific fields of debate relating to the coloniality of the Irish famine. These include the economic structures and dynamics developing over the century before 1845 and the vulnerability of Irish society, the vector of the potato blight and its impact on food availability, and, most extensively, the motivations for and characteristics of British state response to the catastrophe. The variant interpretations of these factors in the nationalist, revisionist, post-revisionist, and post-colonial historiography are reviewed. The author concludes by drawing on his own primary research to suggest that, while shaped by colonial stereotypes and a preoccupation with social engineering, the British state and public response to the Irish crisis was varied and not intentionally genocidal, although ultimately subordinating humanitarianism to perceived British national interest. Critical British contemporaries drew negative parallels between the neglect of Ireland and the prioritization of imperial expansion overseas, while Irish nationalists concluded that the mortality of the famine demonstrated the bankruptcy of the British-Irish Union of 1800.